Prevalence and risk factors of depressive symptoms in latest life: results of the Leipzig Longitudinal Study of the Aged (LEILA 75+) - Luppa, Melanie; Weyerer, Siegfried (International journal of geriatric psychiatry, 2011)
Introduction: Because the oldest old will be the fastest‐growing age group in the future and information about epidemiology of depressive symptoms in latest life is scarce, the present study aims at determining the age‐specific and gender‐specific prevalence rates and risk factors of depressive symptoms in latest life. Methods: As part of the Leipzig Longitudinal Study of the Aged (LEILA 75+), a population‐based sample of 1 006 individuals aged 75 years and older were interviewed on socio‐demographic, clinical and psychometric variables. Depressive symptoms were assessed using the Center for Epidemiologic Studies Depression Scale (cut‐off score ≥16); mild cognitive impairment (MCI) was diagnosed according to criteria of the International Working Group on MCI. Factors associated with depressive symptoms were determined with multiple logistic regression models. Results: Of the overall sample, 38.2% (95% confidence interval, CI 35.2-41.2) were classified as depressed. In the full multivariate model, the following variables were significantly associated with depressive symptoms: divorced or widowed marital status, low educational level, poor self‐rated health status, functional impairment, multi‐domain MCI, stressful life events and poor social network. All variables but MCI remained significant correlates of depressive symptoms in the parsimonious model. Discussion: Because depressive symptoms are common in oldest age and associated with broad categories of risk factors, latest‐life depression represents an important public health issue. Employment of comprehensive geriatric assessment to ascertain depressive symptoms and its concomitants could help to improve treatment success.